Inflammatory disease involving a concha bullosa (enlarged pneumatized middle nasal turbinate): MR and CT appearance. - Lidov, M; Som, P M (American Journal of Neuroradiology, 1990)
An enlarged pneumatized middle turbinate, called a concha bullosa, may be the site of inflammatory disease ranging from simple mucosal thickening to a mucocele. Four patients with inflammatory disease involving a concha bullosa were studied with MR and/or CT. Both imaging techniques detected the presence of mucosal inflammation and a mucocele within the concha bullosa, but CT better demonstrated the thin bony wall of the mucocele, allowing differentiation from other soft-tissue nasal masses.